A clinical study of phenomenology in subjects with pervasive developmental disorders - Chaudhari, Dhananjay; Agarwal, Vivek; Sitholey, Prabhat (International Journal of Research in Medical Sciences, 2018)
Background: Pervasive Developmental Disorders (PDD) are group of developmental disorder with impairments in interaction, communication and behaviour. The study aims to explore the phenomenological aspects of subjects with PDD. Methods: Patients in Psychiatry outpatient department (OPD), presented with impairment in social- interaction, language, communication and mental retardation were assessed for features of PDD by applying Developmental Behaviour Check List (DBCL), ICD-10 Diagnostic Criteria for Research and Multi-Axial version of ICD-10. The subjects were assessed for severity of PDD on Childhood Autism Rating Scale (CARS). Results: Total number of screened positive cases were 20, in which males were over-represented (90%). Majority belonged to urban locality (65%) and nuclear family (75%). Cases of childhood autism were found in all age groups, while childhood disintegrative disorder, Rett’s disorder and atypical autism were found in younger subjects. No family history of PDD was found in 1st degree relatives of PDD subjects. Five subjects (25%) had birth and perinatal complication. Conclusions: The mean age at presentation of the children with PDD was 8.12 years. Eighty percent (80%) of the subjects had severe autism on CARS. Hyperactivity, inattention and impulsivity were present in 90%, 80% and 45% of subjects respectively.